Inovasi Kolaboratif pada Kepemimpinan Bapa Raja dalam Masa Krisis COVID-19 di Bumi Raja-Raja - Marsanty, Dea Alita; Fitriati, Rachma (Research and Development Agency Ministry of Home Affairs, 2023)
The massive and rapid spread of the COVID-19 virus has become a terrible terror for the world community. Various literatures prove the importance of leaders at the lowest level of government (: village heads) as the front guard to break the chain of COVID-19 spread. In Maluku Province, Bapa Raja is not only a traditional leader and community leader who is highly respected by the village community because he was successfully elected through the Village Head Election (Pilkades) mechanism, but also, Bapa Raja must have a royal or sultanate lineage. This study analyzes the collaborative innovation approach to Bapa Raja leadership during the COVID-19 crisis in Maluku Province, known as Bumi Raja-Raja. The research method used a qualitative approach with data collection techniques of observation, literature study, FGDs, and in-depth interviews in 2020-2023. The results showed that Bapa Raja has succeeded in becoming the prominent driving figure in the village in presenting relevant and practical innovations in handling COVID-19 in Maluku Province through integrating, finding, defending, and triggering innovations. Collaborative solid innovation between the government and various stakeholders and active community participation based on local wisdom is the key to success in facing the challenges of the COVID-19 pandemic. This study recommends that the Central Government cq, the Ministry of Home Affairs, make Bapa Raja a role model for other regions due to the success of public services through a collaborative innovation approach in handling the COVID-19 disaster.